2004
DOI: 10.1111/j.1468-0297.2004.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unemployment on Consumption: An Experimental Analysis

Abstract: This paper reports on an experiment that investigates the apparently robust phenomenon of over-sensitivity of consumption to current income. Using a particularly simple formulation, we also investigate whether individuals correctly respond to their employment status. We find that subjects over-react. Our data enables us to investigate where this over-sensitivity originates; we conclude that economic agents differ in their ability to plan ahead and understand the dynamic process determining their employment sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 5 publications
(8 reference statements)
0
76
0
1
Order By: Relevance
“…On the one hand, in Hey and Dardadoni (1988) and Carbone and Hey (2004) the rate of return per period is known and certain, for all money saved. On the other, in Ballinger et al (2004) and Brown et al (2006) the incentives to save money are embedded in their particular utility function, so saving is salient for subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, in Hey and Dardadoni (1988) and Carbone and Hey (2004) the rate of return per period is known and certain, for all money saved. On the other, in Ballinger et al (2004) and Brown et al (2006) the incentives to save money are embedded in their particular utility function, so saving is salient for subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Our paper contributes to the experimental literature dealing with saving-consumption behavior (Camerer and Chua 2005;Carbone and Hey 2004;Ballinger et al 2004;Brown et al 2006). To our knowledge, this is the first experimental approach to examine a dynamic saving-consumption problem in a retirement framework.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies also report on people's difficulties in planning ahead, possibly due to the length of the planning horizon (see Carbone and Hey (2004); Hey and Panaccione (2011) or Hey andKnoll (2007, 2011)). In particular, Ballinger et al (2003) and Carbone and Hey (2004) include a discussion on the estimation of the planning horizon that participants seem to actually use to solve the inter-temporal consumption problem.…”
Section: Introductionmentioning
confidence: 99%
“…Several contributions in the literature, including experimental and empirical studies, have shown how people may have difficulties in optimally solving intertemporal consumption/saving problems 1 . Results have generally shown that participants fail to optimise lifetime utility, in some cases deviating significantly from the optimal consumption strategy (Hey and Dardanoni (1988); Ballinger et al (2003Ballinger et al ( , 2011Carbone and Hey (2004) as well as Brown et al (2009) Experiments on intertemporal consumption/saving problems have typically involved making decisions under risk on the distribution of income (over the life-cycle). In all these cases, participants have knowledge of the stochastic process determining income, no matter the specific procedure (or mechanism) employed.…”
Section: Introductionmentioning
confidence: 99%